Application of fuzzy set theory in the distribution of information flows of a network information system - Robutsov, Alexander V. (Array, 2021)
The subject of this study represents of the processes of functioning of information flows in a network information system through the use of fuzzy sets. The purpose of this article is consider to the possibilities of fuzzy sets in information flows distribution problems of the Network Information System by the development of mathematical tools. In the theoretical part of the study the main issue was the description of fuzzy approach. In the empirical part of the study the main concern was finding out the reasons of the advantages of fuzzy approach. Methods of this research include: analysis of information sources, formalization, synthesis, and modeling. The main results of the present study: proof of the identity between the functioning of the analytical data; held the solution of the optimization problem based on the formulated analytical models; comparison of the usage of fuzzy logic with a different statistical method; demonstrated the advantage of fuzzy approach in modeling processes network information system. The results can be applied to be used by further authors in the field of information systems and technologies. The article is aimed at improving the functioning of the network information system by improving the mathematical tools.